Borderline, white coat and sustained hypertensia: A comparative study a normotensia in personnels of 18-42 year old at Dr. Sardjito General Hospital, Yogyakarta - Suradi Suradi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1997)
A Study of Cross Sectional Survey on 350 subjects from 1216 non physician staffs aged 18-42 at Dr. Sardjito General Hospital was done. There were 51 persons with Borderline Hypertension (15%), consisted of 35 males (68,6%) and 16 females (31,4%), with self monitoring blood pressure at home. The subjects whose average home blood pressure Mean + 1SD and Mean + 2SD, having borderline hypertension had sustained hypertension (SH) and blood pressure while normotensive Mean + 1SD had White Coat Hypertension (WCH). This study found WCH in 25 subjects (49%) and SH 26 subjects (51%). Heart rate of WCH group (83,7-+-5,7) had no significant difference, compared to SH group (86,2 ± 4,1), but was more rapid than normotensive group (74,5 ± 3,6) (p<0.05). There were no significant difference of blood total cholesterol, HDL, LDL, triglyceride between WCH and SH group, but in blood total cholesterol, LDL, triglycerides, were significantly different was compared to normotensive group. A blood HDL of WCH and SH groups had a lower significant different compared to normotensive group (total cholesterol levels 222,4 ± 36,4 vs 217,6 ± 39,7 vs 194,6 ± 33,2), LDL cholesterol (158,2 ± 48,7 vs 156,2 ± 49,1 vs 144,8 ± 33,81, triglycerides (143,6 ± 86,2 vs 146,9 ± 80,2 vs 99,8 ± 51,1). Fasting blood glucose, Insulin and Insulin/glucose ratio in three groups had no significant differences. The conclusions are that total cholesterol, HDL, LDL and triglycerides, and heart rate from WCH group have no significant differences to SH group, but these two groups were significantly different to normotensive group. Fasting blood glucose, insulin, insulin/glucose ratio have no significant difference among the white coat, sustained, and normotensive groups. Key Words: borderline hipertension - white coat hypertension - sustained hypertension - blood chemistry